Impact of land use changes on soil chemical properties, enzyme activities and microbial communities in two contrasting localities of the Argentinian Pampas - Barbero, Florencia Magali; Dominchin, María Florencia; Verdenelli, Romina Aylén; Frasier, Ileana; Restovich, Silvina Beatriz; Campilongo Mancilla, Ernesto Javier; Mlewski, Estela Cecilia; Labuckas, Diana; Vargas Gil, Silvina; Meriles, José Manuel (Elsevier, 2025)
The objective of this work was to study the effect of edaphoclimatic variation in two contrasting localities in response to changes in land use along a gradient of soil disturbance associated with different land use histories. The chosen localities in the Pampas involved both semi-arid (Anguil) and sub-humid (Pergamino) ecoregions, with each locality including four land uses: monoculture (MO), crop rotation with cover crops (RO), pasture (PA), and a pristine environment (PI). Soil chemical properties were significantly influenced by locality, with the lower electrical conductivity values in Pergamino attributed to finer-textured soils retaining more water. In both localities, the highest values of total enzymatic activity (estimated as fluorescein diacetate hydrolase, FDA) were registered under PI, while the lowest were found under MO. The same trend was observed when analyzing C- and N-related enzymes, indicating that these enzymes were significantly decreased under agricultural practices (RO and MO). The highest values of fungal bioindicators were found under PI treatments, suggesting that land use practices can strongly decrease fungal biomass compared to natural grasslands. Total microbial biomass was highest under PI and PA treatments, while agricultural land uses markedly reduced soil microbial biomass. Furthermore, a higher Gram-positive/Gram-negative ratio was observed in Anguil, indicative of diminished nutrient availability and labile substrates. The dominant phyla identified were Proteobacteria, Actinobacteria, Acidobacteria, and Firmicutes, which are commonly found in high abundance across various land-use types. Based on KEGG pathway analysis, Pergamino showed a preference for copiotrophic strategies, while Anguil was more aligned with oligotrophic strategies. This study offers valuable insights into how land use can impact soils in an area known for its suitability for agriculture on a global scale.